Cognitive Behavioral Therapy and Clinical Applications 2018
DOI: 10.5772/intechopen.72146
|View full text |Cite
|
Sign up to set email alerts
|

The Internet and CBT: A New Clinical Application of an Effective Therapy

Abstract: Mental disorders are disabling and common. Depression, for example, has greater global burden of disease than any physical disorder, and almost a third of people will experience some form of mental disorder in their lifetime. The effectiveness of psychological interventions is well established. Cognitive Behavioral Therapy is particularly effective for mood and anxiety disorders. But CBT is demanding of time and resources, partly explaining its limited availability, even in public systems. More and more people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
(104 reference statements)
0
5
0
1
Order By: Relevance
“…The suggestion for increased flexibility of the treatment timeline to meet learning needs is consistent with past research (Rozental et al, 2015). Additionally, Gratzer, Khalid-Khan, and Balasingham (2018) found that working collaboratively with patients to determine timeframes that work best with their schedules and presenting symptoms resulted in the best outcomes. However, other studies have shown that deadline flexibility, where lenience concerning deadlines for homework submission and allowance of extra time to work with a given module, is negatively associated with ICBT symptom outcomes (Paxling et al, 2013; Svartvatten, Segerlund, Dennhag, Andersson, & Carlbring, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The suggestion for increased flexibility of the treatment timeline to meet learning needs is consistent with past research (Rozental et al, 2015). Additionally, Gratzer, Khalid-Khan, and Balasingham (2018) found that working collaboratively with patients to determine timeframes that work best with their schedules and presenting symptoms resulted in the best outcomes. However, other studies have shown that deadline flexibility, where lenience concerning deadlines for homework submission and allowance of extra time to work with a given module, is negatively associated with ICBT symptom outcomes (Paxling et al, 2013; Svartvatten, Segerlund, Dennhag, Andersson, & Carlbring, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The technology also collects in situ assessments of mental health symptoms, which are an ecologically valid source of naturalistic research data [ 8 ]. Online, web-based programs have generated a large evidence base in support of their efficacy and effectiveness [ 9 ], while the evidence in support of mental health apps is still under development [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The technology also collects in situ assessments of mental health symptoms, which are an ecologically valid source of naturalistic research data [8]. Online, web-based programs have generated a large evidence base in support of their efficacy and effectiveness [9], while the evidence in support of mental health apps is still under development [10].…”
Section: Introductionmentioning
confidence: 99%